Autophagy-related proteases accompany the transition of pre-chondrogenic cells into chondroblasts - Ramesova, Alice; Svandova, Eva; Vesela, Barbora; Vacek, Lukas; Lesot, Herve; Matalova, Eva (Annals of anatomy, 2022)
BACKGROUND: Autophagy is classified as a form of programmed cell death. Nevertheless, besides the death-inducing function, autophagy enables removal of damaged organelles, energy savings, and thus cell survival. This applies in particular to cells with poor renewal capabilities, such as chondroblasts. Autophagy is regulated by a complex molecular network, including proteases and their substrates. In autopodium, autophagy-related proteases have been examined particularly within the context of the elimination of the interdigital tissue. However, the death-inducing effects of their expression/activation have not been specified yet. This work focuses on autophagy-associated proteases (cathepsins, matrix metalloproteinases, and caspases) in development of phalangeal cartilage of the mouse autopodium. METHODS: PCR Array, Real-time PCR, and immunohistochemistry were used to follow the expression of autophagy-associated genes in vivo at two developmental stages prenatal/embryonic (E)12 vs. E14. Real-time PCR was then applied to investigate the influence of rapamycin (an inducer of autophagy) on the expression of autophagy-associated proteases in chondroblasts in vitro using micromass culture. RESULTS: Several proteases showed increased expression levels during the transition of pre-chondrogenic cells into chondroblasts in vivo. The most significant increases were observed for Ctsb (fold regulation 2.22), Ctsd (fold regulation 2.37), Ctss (fold regulation 2.92), Mmp9 (up to 445%), and Casp8 (up to 250%). The transition was associated also with the high expression of crucial autophagic inducers, such as Atgs. The in vitro treatment of chondroblasts by rapamycin showed significantly decreased expression of cathepsins, a mild increase in expression of metalloproteinases, and no effect in caspase expression. CONCLUSIONS: The present data provide a screening of autophagy-associated proteases accompanying the formation of cartilage in vivo and specify their expression under rapamycin treatment in vitro. Notably, the selected proteases are assigned to osteoarthritis, therefore their regulation might be used in clinically oriented studies.
Keywords: proteasy; chondrogeneze; Mice; zvířata; Metalloproteinases; apoptóza; Proteases; chondrocyty; Caspases; autofagie; Cathepsins; Cartilage; Peptide Hydrolases; myši; Chondrogenesis; Animals; Autophagy; Chondrocytes; Apoptosis